The evolution of imperfect mimicry in hoverflies - Gilbert, Francis (CABI, 2004)
Ideas about the evolution of imperfect mimicry are reviewed. Their relevance to the colours patterns of hoverflies (Diptera, Syrphidae) are discussed in detail.